TANGGUNG JAWAB PEMERINTAH DALAM MELINDUNGI DOKTER DAN PERAWAT DIMASA PANDEMI - Dipo Pramudito (2022)
Response of a nation in facing a crisis reflects its of system readiness, including the legal and health systems. An undeniable fact is the high mortality rate of Health Human Resources, in Indonesia, in this case Doctors and Nurses while combating the COVID 19 Pandemic Doctors and Nurses are legal subjects, just like other Indonesian people, have the right to health and protection. For Health Human Resources, there are at least five types of protection, especially during the pandemic, namely awarding, protection for occupational health and safety, utilization of health workers, work accident insurance and legal protection. All of them must be done in an integrative way by the government and the government can be sued if they ignore this. This study was conducted to find out whether the government has fulfilled its responsibilities in protecting Doctors and Nurses during a pandemic and to find out what the consequences are if the government fails to provide protection. This research is normative juridical research with data sources from primary legal materials such as legislation, and secondary legal materials such as journals and books. The result of this research is that the government has fulfilled its constitutional responsibilities in protecting Human Resources for Health. The government has deployed preventive and repressive legal instruments in an effort to protect it. The involvement of the community as a component of the nation has been carried out in checks and balances against the protection efforts carried out. Keywords: Responsibility, Protection, Human Resources Health